(untitled) (Research, Society and Development, 2021)
In the ’Information Age’, organizations began to implement knowledge management (KM) practices to gain competitive advantage. Therefore, this research aimed to diagnose the level of implantation and reach of the GC practices of Human Resources in a health care company that performs diagnostic imaging tests in the city of Maringá (PR), Brazil. Methodologically, the research is characterized as a case study, with quantitative and qualitative approaches. For data collection, a questionnaire developed by the Institute of Applied Economic Research (IPEA) was applied and a documentary analysis was also performed. As a result, it was observed that the effective level of implementation and the breadth of reach of the KM practices of human resources were high and that only Corporate Education practice is being used below its potential. With this, some actions were suggested in order to consolidate the practices studied.